Description of the Personality of Amir Temur in Literature - Tadjibaevna, Baltaeva Anadjan; Telmanovna, Khalikberdieva Nargiza (European Journal of Life Safety and Stability (2660-9630), 2022)
Human has always been a central theme of the literature. The article discusses idea of how a great historical person is turned into a main hero in a fiction with all the complexity and controversy of his life in the example of personality of the magnificent Amir Timur and analyzes his relationships with relatives, wives, children, court and officials, as well as the samples of imagery of ruling.